Recontextualization of management policy in indigenous full-time schools in Baja California - Cristian Ernesto Castañeda-Sánchez; Guadalupe Tinajero Villavicencio (Arizona State University, 2020)
This article reports a study on the model of school management followed by indigenous public elementary schools participating in the Full-Time Schools program (PETC) in Baja California, Mexico. It is based on Stephen Ball´s theoretical proposal on policy enactments. The objective was to infer the processes involved in policy interpretation and translation at work when endorsing the PETC policy by supervisor, principals and teachers. From a qualitative perspective, the data consisted of school observations and semi-structured interviews; for their study, we applied James Paul Gee´s analysis of I-statements in order to identify the participants´ stances regarding their everyday schoolwork. The results highlight the restrictions of the contexts under which the program is implemented, as well as the participants' actions taken to fulfill the demands of the PETC, on top of their everyday tasks. In this way, the program and its generic elements are recontextualized in a context marked by historical inequality and marginalization.